Chronic gingivitis and aphthous stomatitis relationship hypothesis: A neuroimmunobiological approach - Chiquita Prahasanti; Nita Margaretha; Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Traumatic injuries to the oral mucosa in fixed orthodontic patients are common, especially in the first week of bracket placement, and occasionally lead to the development of aphthous stomatitis or ulcers. Nevertheless, these lesions are selflimiting. Purpose: The objective of this study is to reveal the connection between chronic gingivitis and aphthous stomatitis which is still unclear. Case: A patient with a persistent lesion for more than six months. Case Management: RAS was treated with scaling procedure, the gingival inflammation was healed. However, in this case report, despite the appropriate management procedures had been done, the lesion still worsen and became more painful. Moreover, the symptoms did not heal for more than two weeks. Actually, they had been undergone orthodontic treatment more than six months and rarely suffered from aphthous stomatitis. Coincidentally, at that time they also suffered from chronic gingivitis. It was interesting that after scaling procedures, the ulcer subsides in two days. Conclusion: Recently, the neuroimmunobiological researches which involved neurotransmitters and cytokines on cell-nerve signaling, and heat shock proteins in gingivitis and stomatitis are in progress. Nevertheless, they were done separately, thus do not explain the interrelationship. This proposed new concept which based on an integrated neuroimmunobiological approach could explain the benefit of periodontal treatment, especially scaling procedures, for avoiding prolonged painful episodes and unnecessary medications in aphthous stomatitis. However, for widely acceptance of the chronic gingivitis and aphthous stomatitis relationship, further clinical and laboratory study should be done. Regarding to the relatively fast healing after scaling procedures in this case report; it was concluded that the connection between chronic gingivitis and aphthous stomatitis is possible.